Preparation and wear assessment of ultrasonic electrodeposited Ni–TiN thin films. Issue 10 (July 2018) - Xia, Fafeng; Yang, Anna; Cui, Wei; Li, Qiang
Abstract: In this study, pure Ni and Ni–TiN thin films were prefabricated from a reformative Watt nickel bath through ultrasonic electrodeposition (UE) under pulse current (PC) condition. The effects of ultrasonic intensity on surface morphology, microstructure and phase composition were evaluated through scanning electron microscopy (SEM), scanning probe microscopy (SPM), transmission electron microscopy (TEM) and X-ray diffraction (XRD). The Vickers hardness, the friction coefficient and the wear resistance of Ni and Ni–TiN thin films were also estimated. All SEM, SPM, and TEM results demonstrated that the Ni-TiN thin film obtained at the ultrasonic intensity of 30 W/cm 2 had a fine, smooth and homogeneous surface morphology. The root-mean-square roughness ( Rms ) and arithmetic mean roughness ( Ra ) of the film with a surface area of 4.096 µm 2 were 36.813 nm and 22.836 nm, respectively. Also, the mean diameters of Ni grains and TiN nanoparticles were approximately 46.7 nm and 23.2 nm, respectively. The XRD analysis indicated that the XRD patterns of the films prepared with different plating parameters had the same diffraction angle with the Ni phase except the diffraction intensity. Microhardness tests exhibited that the Ni film displayed the minimum microhardness value of 38.6 HV. Moreover, the Ni-TiN film obtained at the ultrasonic intensity of 30 W/cm 2 acquired the maximum microhardness value of 912.1 HV. The wear behavior assessment demonstrated that the Ni-TiN film prefabricated at the ultrasonic intensity of 30 W/cm 2 sustained the least weight loss, while the mean friction coefficient was approximately 0.39, thereby displaying the best wear resistance.